Tuha Peut dalam Pemerintahan Gampong di Hagu Selatan Kota Lhokseumawe Tahun 2008-2014 - SRI MAULIZAR (Universitas Sumatera Utara, 2015)
This study is pertaining of Tuha Peut in the Village Government in Hagu Selatan Lhokseumawe City for the Year period of2007-2014. Tuha Peut is the person who becomes the leader of com-munity. It is the lowest level from the hierarchy of the local government in Hagu Selatan. The focus discussion of the study is to answer the question; what are the causes of Tuha Peut not function effectively in accordance with the existing provisions in Hagu Selatan Lhokseumawe city. The study found that there are several essential facts, some of them,are; the existence of a communication gap between Keuchik and Tuha Peut; then, the lacking of leadership factor. The study shows that Keuchik failed to deliver and provide the guidance for the Tuha Peut in order to execute all the tasks. The used method of the study is descriptive-qualitative method. The technic of data gathering was the field research and the documentary study.Keywords: Tuha Peut, the village government, keuchik.